Vaginal Microbiota Changes Caused by HPV Infection in Chinese Women - Zhang, Yichan; Xu, Xiaolin; Yu, Liqun; Shi, Xingxian; Min, Min; Xiong, Lijuan; Pan, Jia; Zhang, Yong; Liu, Peipei; Wu, Guizhen; Gao, Guolan (Frontiers in Cellular and Infection Microbiology, 2022)
Human papillomavirus (HPV) infection is one of the most common sexually transmitted diseases. After studied 602 unvaccinated Chinese women using 16s rRNA to detect cervical-vaginal microecology, we analyzed the relationship between HPV infection and vaginal microecology including 20 HPV types. In Chinese women, L. gasseri-dominated and L. jensenii-dominated clusters were significantly absence. Microbial alpha diversity was significantly higher in HPV infection and CIN diagnosed groups than in healthy control group. Certain bacteria were associated with HPV infection and CIN diagnosed, including Streptococcus, Prevotella, Chlamydia, Bifidobacterium, Ralstonia and Aerococcus. With the development of disease, the proportions of CST-III and CST-IV-B gradually increased, while the proportions of CST-I and CST-IV-A gradually decreased. In addition, age was an influential factor for HPV infection. With aging, the probability of HPV infection and the proportion of CST-IV-B increase. In conclusion, our study was a large cross-sectional study that evaluated the relationship between vaginal microbiota and HPV infection, and brought essential comparable data.